Efektivitas Kegiatan Program Ekstrakurikuler Keagamaan Tilawah Al- Qur’an dalam Meningkatkan Kemampuan Baca Tulis Al-Qur’an Santri di Pondok Pesantren Ar- Raudhatul Hasanah - Neliwati; A Zeni Azima; Dea Yolanda Damanik; Shofiyah Nabilah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Through extracurricular religious program activities in Islamic boarding schools, the aim is to enable children to broaden their knowledge of Islamic religious education and motivate students to increase their level of religiousness by participating in extracurricular activities. In addition to being able to develop the talents, interests and skills possessed by students. This research method uses a qualitative approach with data collection techniques obtained by interviews, observation and documentation. The results of this research indicate that the aim of the PAI extracurricular activity is Al-Qur'an Recitations, apart from forming and deepening the students' superior skills in the field of Al-Qur'an recitations, this extracurricular activity also aims to sharpen and demonstrate the students' abilities in reading and writing the Al-Qur'an. and the abilities of the students who take part in these extracurricular activities make them an advantage in the organization. Many of them become mosque imams and get good positions in organizations such as the field of security education and especially mosque uncleanliness.